The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.2147/nss.s314769
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Vigilant Attention Partly Accounts for Inhibition Control Deficits After Total Sleep Deprivation and Partial Sleep Restriction

Abstract: Purpose Sleep loss impairs a range of neurobehavioral functions, particularly vigilant attention and arousal. However, the detrimental effects of sleep deprivation on inhibition control and its relationship to vigilant attention impairments remain unclear. This study examined the extent to which vigilant attention deficits contribute to inhibition control performance after one night of total sleep deprivation (TSD) and two nights of partial sleep restriction (PSR). Participants and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…Previous studies reported attention deficits, memory problems, and impaired executive functions after either total or partial sleep deprivation. 17 , 33 , 34 It is known that patients with mTBI can suffer from long-term cognitive difficulties and lower quality of life. This study showed that moderate-severe sleep disturbances are associated with delayed recovery of cognitive functions and unfavorable long-term outcomes post-mTBI.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported attention deficits, memory problems, and impaired executive functions after either total or partial sleep deprivation. 17 , 33 , 34 It is known that patients with mTBI can suffer from long-term cognitive difficulties and lower quality of life. This study showed that moderate-severe sleep disturbances are associated with delayed recovery of cognitive functions and unfavorable long-term outcomes post-mTBI.…”
Section: Discussionmentioning
confidence: 99%
“…However, the advent of 24/7 technology and increasingly demanding daily routines has led to widespread sleep loss, which has been a major public health concern in the contemporary society. Numerous studies have consistently demonstrated that lack of sleep results in significant performance deficits across a broad range of neurocognitive functions, particularly vigilant attention, motor responses, inhibition control, and working memory (Chee & Choo, 2004; Czisch et al., 2012; Dinges et al., 1997; Eide et al., 2021; Goel et al., 2009, 2013; Hudson et al., 2020; Liew & Aung, 2021; Mao et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It also has important implications for understanding the degree to which sleep deprivation effects are generally driven by vigilant attention deficits, even on tasks other than those measuring vigilant attention (cf. Mao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%